Do foreigners replace native immigrants? Evidence from a panel cointegration analysis - Herbert Brücker; Stefano Fachin; Alessandra Venturini (Institute for the Study of Labor (IZA), 2009)
This paper examines the impact of the immigration of foreigners on domestic labour mobility. Since David Card's seminal study on the regional labour market impact of the Mariel Boatlift it is controversial whether domestic labour mobility equilibrates economic conditions across cities and regions. However, there is little or no evidence that natives leave destinations where migrants tend to cluster. In this paper we reconcile the existing evidence by taking another route. We analyze whether the immigration of foreigners replaces domestic mobility from poor to rich regions. We focus on Italy, which is characterized by market differences in earnings between the North and the South. Based on a panel cointegration approach we exploit the variance of international and internal migration over time for identifying potential displacement effects. The main finding is that, conditional on unemployment and wage differentials, the share of foreign workers in the labour force of the destination regions discourages internal labour mobility significantly. As a consequence, spatial correlation studies which use the variance of the foreigner share across region for identifying the wage and employment effects of immigration, tend to understate the actual immigration impact.
urn:nbn:de:101:1-200910141174
Keywords: F22; 330; International migration; domestic migration; labour markets; panel cointegration; Italy; Einwanderung; Internationale Wanderung; Binnenwanderung; Ausländische Arbeitskräfte; Regionale Arbeitsmobilität; Arbeitsmarkt; Schätzung; Italien